An Introduction to Cooperation and Mutualism - Boland, Michael (Open textbook library., 2017)
This textbook introduces readers to the idea of cooperation and mutualism. Cooperatives and mutuals are participatory organizations in which members participate in control and governance, receive economic benefits through patronage refunds or net income, and become owners through equity. These mutual-benefit organizations exist alongside non-profit organizations and investor-benefit organizations through the global economy.